Implementation of Wakalah bi al-Ujrah Contract in COD Transactions on Shopee: A Review Based on MUI Fatwa - Lahuri, Setiawan Bin; Handayani, Agung Lia (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2023)
This research aims to analyze the contract used for Cash on Delivery (COD) payments on the Shopee Online Shop platform, with a focus on integration with the principles of the wakalah bi al-ujrah contract explained in DSN-MUI Fatwa No. 113/DSN-MUI/IX/2017. The research method used is data collection and literature study with a description approach. The analysis results show that the COD practice on Shopee follows the pattern of buying and selling transactions between sellers and buyers using expedition services as intermediaries, using the basic concept of at-tackle fil. This research concludes that the general provisions of the COD payment method on Shopee are the general provisions of the wakalah bi al-ujrah contract because they fulfill the elements regulated in the DSN MUI Fatwa Number 113/DSN-MUI/IX/2017. The implication of this research is to strengthen understanding of e-commerce platforms' compliance with Sharia principles in COD payment systems, which can provide users more confidence and trust in online transactions.